Proecological dispersions for surface modification of cellulosic materials. Part I, Preparation and properties of aqueous film-forming dispersions of Candelilla wax - Romanowska-Osuch, A.; Bartkowiak, A. (Polimery, 2011)
Aqueous dispersions (25 %) of natural hydrophobic Candelilla wax has been prepared with various emulsifiers: low molecular (non-ionic and anionic) and macromolecular (protein and polysaccharide). The dispersions were obtained using ultrasonic homogenization, and the resulting emulsions were applied for the modification of porous „inner” side of cellulosic material (paperboard). By mixing the emulsions with biopolymer carrier (starch sodium octenyl succinate — OSA), film-forming compositions were obtained, having an appropriate viscosity to form high-quality coatings. More homogeneous emulsions were prepared using soy protein and anionic emulsifier, while the systems with non-ionic emulsifier Tween 20 showed the best barrier properties. Particle size measurements indicated that the most favourable conditions for obtaining Candelilla emulsions were: temperature of 90 °C and sonication time of 5 minutes. The most stable dispersion was obtained using 25 % Candelilla wax/water emulsion containing 4 % emulsifier Tween 20.